Towards collisions : an enhanced successive interference cancellation with asynchronism - Li, Qiang. (2013)
In this paper, we consider a hidden terminal scenario where two transmitters A and B, hidden to each other, wish to communicate to a common access point, AP. When a collision occurs at AP, due to the inherent asynchrony between the colliding packets, the mutual interference between them is effectively decreased. This achieves a higher signal-to-interference-plus-noise (SINR) ratio which improves the probability of successfully decoding both colliding packets through conventional successive interference cancellation (SIC). When neither colliding packet can be decoded first through SIC, we propose an enhanced SIC (ESIC) scheme. The proposed decoding scheme does not require synchronization, coordination or power control between the transmitters or a sophisticated coding design. By exploiting the inherent asynchrony between the two colliding packets, there exists, with high probability, an interference-free chunk together with an interfered chunk in a packet ready for decoding. Thus it is still possible for both colliding packets to be recovered eventually from a single collision. Our results demonstrate that through the proposed ESIC scheme, both colliding packets can be recovered with a higher probability thus improving the system throughput.